Effect of selected exercises on flexibility and coordination of volleyball players - Majeed, A.; Bhat, M. A.; Sayar, P. S. (2021)
The main purpose of the study was to study the effect of selected exercises on flexibility and coordination of volleyball players. The age of the players was ranging from 17- 22 years. Only 40 male players were selected for the study. A total period of six weeks training was administered on the experimental groups. The subjects were selected from Kulgam district of Jammu and Kashmir volleyball players. The variables selected for this study were trunk flexibility, eye hand coordination and eye foot coordination. `t` test was used for analysis of data at 0.05 level of significance. It was hypothesized that there might be a significant effect of certain selected exercises on flexibility and coordination of basketball players.